Znaczenie religii w ateistycznej filozofii Hegla - Szocik, Konrad (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2012)
Hegel's philosophy of religion is typical for critical philosophy of Enlightenment. Hegel treatsabout religion as an earlier and less developed form of human mind. Religion is product of culture,society and mythological mind, which is connected with emotions and imagination.